O GÊNERO QUESNELIA GAUDICH. (BROMELIACEAE-BROMELIOIDEAE) NO ESTADO DO PARANÁ, BRASIL: ASPECTOS TAXONÔMICOS E ANATÔMICOS - Oliveira, Fernanda Maria Cordeiro de (2012)
The genus Quesnelia belongs to the subfamily Bromelioideae, with 20 species, distributed since the south of Bahia to the north of Santa Catarina. The genus is divided into two subgenera: Quesnelia subg. Quesnelia and Quesnelia subg. Billbergiopsis Mez. A taxonomic study of the genera was done to the State of Paraná, based in material in vivo and in exemplars of herbarium collections. It was recognized three taxa in the state: Quesnelia testudo Lindm, Quesnelia humilis Mez e Quesnelia imbricata L.B.Sm, presenting different life forms and geographical distribution. It was done an anatomical study of vegetative organs that shows adaptive strategies to the rupicolous and epiphytic habits of the studied species and characters that can be useful in future studies of taxonomy in the group.